Digital Classroom Management in Geography Education: A Case Study of a Smart Digital Madrasah in Indonesia - Fitri Aprilianty; Tri Widayatsih; Mahasir Mahasir (Yayasan Sembilan Pemuda Indonesia, 2026)
This study aims to analyze the comprehensive framework of digital classroom management in Geography subjects at SMART Digital Madrasah MAN 3 Palembang, focusing on planning, implementation, evaluation, and encountered challenges. Using a qualitative case study design, data were collected through in-depth interviews, participant observation, and documentation from key informants, including administrators and teachers, with analysis following thematic stages. The results reveal a systematically planned ecosystem involving infrastructure readiness, a dedicated teacher upskilling program (“BURGO”), and digital administrative tools. Implementation utilizes a Blended Learning model that integrates real and virtual digital classes with platforms like Google Earth and Quizizz. Evaluation is digitally embedded through creative and gamified assessments, alongside a computerized testing system. A critical finding is the gap between ideal planning and practical constraints, primarily limited internet bandwidth for large-scale student access. The study’s novelty lies in its holistic examination of digital management within a madrasah context, proposing an integrated four-pillar model. Practically, it offers a replicable blueprint for similar institutions undergoing digital transformation. Its main contribution is enriching the literature on sustainable digital integration in faith-based educational settings, highlighting both strategic enablers and infrastructural prerequisites.